Magnetic Driven Double Curved Conical Microhelical Robot. Issue 12 (13th October 2021) - Lin, Jieqiong; Zhu, Zhenyan; Jing, Xian; Lu, Mingming; Gu, Yan
Abstract: The swimming performance of the magnetic driven microhelical robot is mainly determined by its geometric structure. In this research, the existing swimming mathematical model of the microhelical robot is extended by the microelement method, so that it can be used to calculate the swimming speed of the double curved conical microhelical robot (DCCMHR) below the step‐out frequency. Then, the swimming performance of the microhelical robot with different geometric characteristics is explored through simulation experiments, and the structure of DCCMHR is further optimized by analyzing the influence of geometric parameters such as helix angle, helical length, helical wire diameter, cone angle, and the number of thread on the swimming performance of the robot. Compared with the traditional microhelical robot, the swimming speed of the improved microhelical robot can be increased by about 1.2 times, and the stability can be increased by about 25%, which provides a good foundation for the future application of microhelical robot in complex environment, such as minimally invasive surgery, drug delivery, cell transportation, living detection and so on. Abstract : A mathematical model for calculating the swimming speed of the double curved conical microhelical robot (DCCMHR) below the step‐out frequency is proposed. The swimming performance of the microhelical robot with different geometric characteristics is explored through simulation, and the structure of DCCMHR is further optimized by analyzing the influence of geometric parameters on the swimming performance of the robot.